A proposed framework of school inspection outcomes: understanding effects of school inspection and potential ways to facilitate school improvement - Md Ali, Nurul Jawahir; Abdul Kadir, Suhaida; Eric Krauss, Steven; Basri, Ramli; Abdullah, Arnida (Human Resource Management Academic Research Society, 2021)
This paper aims to develop a framework of school inspection outcomes by reviewing two models of school inspection effects towards school. The first framework by Ehren and Visscher (2006) describes school inspection as a process connected through features of school inspection, external impulses and support, school features, school reaction and its effects. The second model by Landwehr (2011) describes the benefits of school inspection as primary instrument for gaining knowledge, accountability, enforcing standard and school development and presents the school inspection desirable outcomes at its best. These two models then are combined together and a framework of school inspection outcome is proposed. This framework then may provide ground for future studies that wishes to study school inspection effects on school as well as to explore the potential ways to improve school inspection practices to optimize its contribution on school improvement.